Internal Security and National Development in Nigeria: Challenges of Manpower in Nigeria Police - Oikhala, Gabriel Izokpu (NIU Journal of Humanities; Vol 5 No 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
Safeguarding citizens and providing their welfare needs are functions of government across the globe. When citizens are faced with dwindling security, they lose confidence and hope in such government. In Nigeria, the 1999 Constitution recognised the police as the lead agency for internal security architecture. However, the narrative in recent time has been on the staggering manpower shortage of the police causing its inability to curb the flurry incidence of kidnapping, armed robbery, herdsmen carnage, and terrorism among other security challenges threatening the people and proper functioning of the country. The paper examined the implication of the police manpower shortage on security and national development. Data were obtained from relevant journals, textbooks, newspapers, and other publications. Analysis of the data gathered was done through descriptive method. Using the structural functionalism theory as the theoretical framework, the federal government is identified as principal agent of the state with functions to superintend and maintain the police system for proper functioning. The paper found a strong correlation between police manpower shortage and development challenges of Nigeria especially in the fourth republic. It argued among others that failure of the federal government to equip the police with adequate manpower is responsible for decline of development in Nigeria. The paper concluded that there will be no hope of security and progress for a country that is operating a defective police system. Therefore, there should be a reform of the police to improve on the manpower strength. Keywords: Internal Security, Police, Manpower, National Development, Government